Factors influencing international student mobility: lesson learned from Malaysian public higher institution - Govindan, Subramaniam; Mohd Isa, Salmi; Mohd Nasir, Nur Farah Wani (GADING Journal for the Social Sciences, 2023)
The international student market is growing exponentially. A growing number of offered higher education at home and abroad contributes to increasing competition in the international student market. To attract prospective students, Malaysian public universities must differentiate themselves from their competitors. To this end, they are developing and implementing international mobility programs to tap into new markets. Currently, the motivating factors in the decision-making process for students to study abroad include student expectations, self-efficacy, and social media role. Through empirically studying five Malaysian public higher education institutions with 309 international students, this study provides a comprehensive overview of the current patterns of international student mobility. Interestingly, social media does not influence destination image and intention to use international student mobility programs. Students’ expectations and self-efficacy reveal significant future trends influencing mobility programs.